In Vitro and In Vivo Tests of the Cidal Effects of Certain Agents for Hydatid Protoscolices. - Al-Muathen, Dhilal Mahdi (Al-Nahrain Journal of Science, 2018)
Cysts from the liver of hydatidosis infected sheep were obtained from a local abattoir, live protoscolices were prepared by using of Kreb’s Ringer solution plus Hydatid Cyst Fluid (4:1) and exposed to selected protoscolicidal agents (Mebendazole 5%, Cetrimide 0.15%, and Formaline 2%) in vitro, survival times of protoscolices in the presence of chemicals was used as a criterion of protoscolicidal agents activity by using eosin stain. After treatment it was concluded that all the treated protoscolices of the study were completely killed with Mebendazole 5% and Cetrimide 0.15% at 5 minutes of exposure, while Formaline 2% did not cause complete killing even at 15 min of exposure. furthermore the results of in vivo part of this study showed that all the treated scolices in vitro part were completely killed and did not cause hydatidosis up to 90 days post infection in laboratory albino mice.